What Do Participants of the Crohn's and Colitis UK (CCUK) Annual York Walk Think of Their Inflammatory Bowel Disease Care? A Short Report on a Survey. (January 2018) - Mikocka-Walus, Antonina; Power, Madeleine; Rook, Lisa; Robins, Gerry
Abstract : There has been a growing interest in a patient-centered model of care in inflammatory bowel disease; however, no relevant study using a mixed methodology has been conducted to date. Thus, our multidisciplinary group aimed to explore the issue of patient involvement in care among the inflammatory bowel disease community. A mixed-methods anonymous survey was conducted during the Crohn's and Colitis UK annual event. Summary statistics were used to describe the sample, and a simple thematic analysis identified key themes in qualitative responses. There were 64 survey respondents, representing 73% of the total family/friend groups participating ( N = 87). Overall, 75% of respondents answered that they had the opportunity to discuss their care with their inflammatory bowel disease practitioner and 81% felt their opinions were taken on board and valued. A clear majority (84%) had at some point been treated by a gastroenterologist. In contrast, less than half (44%) had the opportunity for a dietician consultation and only 28% had the opportunity for a psychologist/counselor consultation. Although satisfaction with inflammatory bowel disease care was high, access to specialty services was concerning. Efforts should be made to provide access to mental health practitioners for those with clinically significant anxiety and/or depression.